2018
DOI: 10.1097/md.0000000000012455
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of decreased NDRG1 expression in patients with digestive system cancers

Abstract: Background:Digestive system cancers are recognized as associated with high morbidity and mortality. It is generally accepted that N-myc downstream-regulated gene 1 (NDRG1) is aberrantly overexpressed or downregulated in digestive system cancers, and its prognostic value remains controversial. Accordingly, we herein conducted a meta-analysis to explore whether NDRG1 expression is correlated with overall survival (OS) and clinicopathological characteristics of patients with digestive system cancers.Methods:We sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Indeed, both overall survival (OS) and cancer-free survival (CFS) are lower in CRC patients with low NDRG1 expression compared to those with high NDRG1 expression. This indicates that NDRG1 expression is positively linked to both OS and CFS in CRC patients. , As shown by the NDRG1 function and expression in CRC cells, regulation of NDRG1 expression can be a plausible way to treat CRC. Therefore, the effects of 1 on modulation of NDRG1 expression were evaluated in CRC cells.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Indeed, both overall survival (OS) and cancer-free survival (CFS) are lower in CRC patients with low NDRG1 expression compared to those with high NDRG1 expression. This indicates that NDRG1 expression is positively linked to both OS and CFS in CRC patients. , As shown by the NDRG1 function and expression in CRC cells, regulation of NDRG1 expression can be a plausible way to treat CRC. Therefore, the effects of 1 on modulation of NDRG1 expression were evaluated in CRC cells.…”
Section: Resultsmentioning
confidence: 84%
“…N-myc downstream-regulated gene 1 (NDRG1) is an effective metastasis suppressor in a variety of cancer types . Evidence has demonstrated that cancer cell proliferation, cell-cycle regulation, apoptosis, and metastasis are related to NDRG1 expression. NDRG1 expression has been significantly lower in various malignancies, including prostate, breast, and CRC. Furthermore, NDRG1 overexpression inhibited CRC cell invasion and metastasis, and thus is negatively correlated with CRC prognosis. , One of the oncogenes most often overexpressed in human malignancies is c-Myc, and c-Myc transcription factor regulates several target genes in cell proliferation, growth, and transformation . Increased genomic instability, angiogenesis, and differentiation blockage have been correlated with the dysregulation of c-Myc.…”
mentioning
confidence: 99%
“…Digestive system tumors have high morbidity and mortality and account for a large proportion of all tumors[1,2]. It has been confirmed that some non-coding RNAs (ncRNAs) are engaged in the pathogenesis of digestive system tumors, and elucidating the role of these ncRNAs can help to understand the potential pathogenesis of digestive system tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Also, 2 cells in allergic disease could increase Hsp70, which was involved in pathogenesis [29]. N-myc downregulated 1 (NDRG1) was a tumor suppressor, which has been reported in various studies; it could attenuate NF-kB and TGF-b pathways in pancreatic cancer cells, and downregulated NDRG1 was related to increased proliferation, invasion, and migration of digestive cancers [30][31][32][33]. It additionally involves apoptosis, glycolytic, and lipid metabolism in cancer cells, and virus infection process was also related to NDRG1 [34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%